Technological optimization of fully mechanized caving mining face with large mining heights - Fan, Lu-Jia; Yang, Sheng-Li (Journal of coal science & engineering, China, 2013)
Fully mechanized cave mining with large mining height is a new mining method, due to its large mining thickness and lower roadway excavation, the technology has been widely used in China＇s thick seam mining. In order to improve the top-coal recovery ratio of fully mechanized cave mining with large mining height, a study was conducted on optimizing the caving process, based on the mechanized caving face 1302N in Longgu Coal Mine. This was achieved by improving the PFC numerical calculation methods, and establishing a more accurate model system. On this basis, the recovery ratio of the top coal in different drawing intervals and technologies was investigated in order to achieve a reasonable caving process. The top-coal tracking system was used for practical surveying of the recovery ratio of top coal.